Effect of Triblock Copolymer on Carbon-Based Boron Nitride Whiskers for Efficient CO(2) Adsorption - Kamran, Urooj (Polymers (Basel), 2019)
Herein, we investigated novel carbon-containing P123 copolymer-activated boron nitride whiskers (P123-CBNW) fabricated via a structure directing approach followed by a single-step heat treatment under N(2). The resulting materials were found to be highly micro- and mesoporous. The influence of the activating agent (P123 copolymer) on the CO(2) adsorption efficiency was determined. The prepared samples possessed high specific surface areas (594–1732 m(2)/g) and micropore volumes (0.258–0.672 cm(3)/g). The maximum CO(2) uptakes of the prepared adsorbents were in the range 136–308 mg/g (3.09–7.01 mmol/g) at 273 K and 1 bar and 97–114 mg/g (2.22–4.62 mmol/g) in the following order: CBNW < P123-CBNW3 < P123-CBNW2 < P123-CBNW1 < P123-CBNW0.5. The isosteric heat of adsorption values (∆Q(st)) were found to be 33.7–43.7 kJ/mol, demonstrating the physisorption nature of the CO(2) adsorption. Extensive analysis revealed that the presence of carbon, the high specific surface area, the high microporosity, and the chemical structural defects within the adsorbents are responsible for raising the CO(2) adsorption ability and the selectivity over N(2) gas. The fabricated adsorbents show excellent regeneration ability after several repeated adsorption cycles, making the prepared adsorbents promising candidates for gas storage applications.